PENGARUH LAMA PROSES PENYIMPANAN TERHADAP KUALITAS DODOL KACANG MERAH - Anita Dimu Lobo; Isak F Alelang; Indrayati Juma (Politeknik Pertanian Negeri Kupang, 2022)
The long effects of the storage process on the quality of red beans dodol. Peanut butter is a processed product made of peanut flour, glutianous flour and other additives such as brown sugar, sugar, salt, and coconut milk. The study was aimed at identifying the effects of the long storage process on the quality of the dans’dodol determine the best treatment of red-bean storage. The study employed a complete random (RAL) method of design based on the use of red bean flour in the manufacture of 1 day, 2 days, 4 days, 6 days with each treatment repeated over 3 times to make it 12 experimental units. Analysis using fingerprints (Anova) suggests that the effects of treatment are profound real ( fi>1%) the texture, color, scent and Tate of red bean paste. Treatment A is highly desirable to the consumer, which is average against texture 4,00, color 4,00, scent 3,67, and taste 4,0.Keywards : Mreah bean flour, lunkhead, organical muffler.